The effect of age to the perception of apparent usability and affective quality on prototype mobile phones - Seva, Rosemary R. (Animo Repository, 2019)
In this study, a design framework that integrates functional and aesthetic attributes with apparent usability and affective quality was validated using prototypes. The framework was validated using a mobile phone which is a high involvement product. Product attributes that affected visual evaluation prior to usage were selected and categorized into functional and aesthetic attributes. Nine design alternatives were generated out of varied functional and aesthetic design attributes. A survey was used to evaluated each design alternative in terms of the pre-purchase dimensions of affective quality, apparent usability, and desirability. Structural equation modeling (SEM) was used to validate the design framework. After conducting the experiment, the model obtained has a good fit and the relationships were significant. It was found that affective quality has the greatest direct effect on desirability and apparent usability has the greatest total effect on desirability. Functional attributes have significant total effects on apparent usability and desirability. For comparative analysis, older people’s perception on functional attributes have a greater effect on apparent usability, affective quality and desirability. Finally, it can be said that apparent usability evokes more emotions for people having greater usability needs such as older people. © Springer Nature Switzerland AG 2019.